2021
DOI: 10.1007/s00784-020-03771-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronic acid on paracrine signaling of osteoblasts from mesenchymal stromal cells: potential impact on bone regeneration

Abstract: Objectives This study evaluated hyaluronic acids (HA) with different molecular weights as potential matrices for tissue-engineered bone grafting and their possible influence on the paracrine mechanisms of adipose-derived mesenchymal stromal cells. Material and methods Murine adipose mesenchymal stromal cells (mASCs) on the fourth passage were seeded in 96-well plates, osteoinduced for 27 days and exposed for 3 days to low (HA-LW) and high/low molecular weight (HA-HLW) at previously defined concentrations. Cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similarly, HA promotes bone regeneration by influencing cell proliferation and osteogenic differentiation. In a review of the literature, it was found that HA could be positive for the expression of BMP-2 or other osteoprogenitor and osteogenic markers as it provides an ideal environment by virtue of its physicochemical properties (Nickel and Mueller, 2017;Matheus et al, 2020;Cabreira et al, 2021). In this study, the expression of BMP-2 was upregulated at 4 and 8 weeks.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, HA promotes bone regeneration by influencing cell proliferation and osteogenic differentiation. In a review of the literature, it was found that HA could be positive for the expression of BMP-2 or other osteoprogenitor and osteogenic markers as it provides an ideal environment by virtue of its physicochemical properties (Nickel and Mueller, 2017;Matheus et al, 2020;Cabreira et al, 2021). In this study, the expression of BMP-2 was upregulated at 4 and 8 weeks.…”
Section: Discussionmentioning
confidence: 54%